2006
DOI: 10.1002/chem.200600437
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of Peroxoborates: Borate Inhibition of the Photodecomposition of Hydrogen Peroxide

Abstract: The UV absorbance and photochemical decomposition kinetics of hydrogen peroxide in borate/boric acid buffers were investigated as a function of pH, total peroxide concentration, and total boron concentration. At higher pH borate/boric acid inhibits the photodecomposition of hydrogen peroxide (molar absorptivity and quantum yield of H(2)O(2) and HO(2) (-), (19.0+/-0.3) M(-1) cm(-1) and 1, and (237+/-7) M(-1) cm(-1) and 0.8+/-0.1, respectively). The results are consistent with the equilibrium formation of the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Therefore, under the experimental conditions used in this study, the amount of peroxoborates formed may be negligible. It has also been shown that borate and boric acid have insignificant rates of reaction with hydroxyl radicals as compared with hydrogen peroxide and thus cannot act as free radical scavengers in the decomposition of hydrogen peroxide (25).…”
Section: Oxidation Of Trpmentioning
confidence: 99%
“…Therefore, under the experimental conditions used in this study, the amount of peroxoborates formed may be negligible. It has also been shown that borate and boric acid have insignificant rates of reaction with hydroxyl radicals as compared with hydrogen peroxide and thus cannot act as free radical scavengers in the decomposition of hydrogen peroxide (25).…”
Section: Oxidation Of Trpmentioning
confidence: 99%
“…k OHb(BB) in eqn (4), the mechanism shown in Scheme 3 would facilitate the leaving of the peroxide group as monoperoxodiborate, which is known from the literature. 48 It is possible that there may be a pre-association of one of the boric acids with the outer peroxo oxygen of the peracetic acid anion prior to the transition state, thus avoiding the requirement for three molecules in the transition state (McKillop and Sanderson have proposed a similar structure, though for non-aqueous conditions 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…Rey and Davies (2006) [ 21 ] investigated the kinetics of the photochemically-induced decomposition of H 2 O 2 in borate buffer solutions as a function of reactant concentrations and pH (Equation (2)), and discovered that borate effectively suppressed this photodegradation process at the higher pH values studied. These results were concordant with the generation of mono-peroxoborate and mono-peroxodiborate anions ([B(OH) 3 (O 2 H)] − and [(HO) 3 BOOB(OH) 3 ] 2− respectively), with thermodynamic equilibrium constants for their formation being 2.0 × 10 −8 for [B(OH) 3 (O 2 H)] − [ 13 ], and conditionally-dependent values of 1.0 or 4.3 for [(HO) 3 BOOB(OH) 3 ] 2− .…”
Section: Peroxoborate Photochemistrymentioning
confidence: 99%